Different Approaches to Inflation Forecasting in Argentina - Basco, Emiliano (2015)
We apply some recently developed and more traditional methods to forecast in ation in Argentina and compare their predictive ability at di¤erent horizons. Our variety of models includes: (i) Traditional time series models -AR(1) and a monetary VAR-, (ii) a factor model combining a large number of business cycle indicators and (iii) micro-funded models including a conventional New Keynesian Phillips Curve and one that incorporates money to evaluate its information content as a predictor of in ation. We compare the predictive performance of the di¤erent methods using the Giacomini-White test over the relevant horizons for monetary policy decisions. We nd that the monetary VAR outperforms the rest of the models.